رەنگ لە شیعری گۆران و نیمایوشیج دا (توێژینەوەیەكی بەراوردكاری) - تەها, عەدنان عەبدولڕەحمان; محمد, شنۆ محمود (Sulaimani Journal for Humanities, 2025)
Humans are under the influence of the environment that they live. This always makes human’s attention and love excited. Through the strength of the colour, poet expresses his/her love, fear, anger and etc…For ages, colour is the most outstanding and sensible element that draws the attention of the humans in general and the poets particularly. Colour becomes a major factor in making creativity of the poets. Colour is the source of calmness and the climax of the beauty in the world of human beings. Meanwhile, as an aesthete and sensible person, the poets get benefits from the colour in strengthening the images of their poems, or they use it as a symbol for those concepts in which they cannot express them directly. For instance, this is existed when the poems are constantly under the observation of the dictators. Colour is a noticeable symbol of the objects that can be seen easily. Everyone has their own understanding for colour based on their background and speciality. All the poets and particularly both Goran and Nimayushij have their own viewpoint for colour in which colour extends to their essences because their points of view are basically different from the others. That is why, by using different languages and the selecting strange words, the poet’s language is different from the language of common people and write their poems consequently. So, colour has a great role in writing poems.